Analysis of Cyanide Content on Yams Using Spectrophotometry Methods - Vany Widiastuti; Erlin Ernawati; Vita Fatmadewi; Saraswati Anindyajati; Shaaliyah Novita Faradina (Universitas Negeri Yogyakarta, 2018)
This study aims to determine whether or not cyanide content in various species of yams in the District of Tempel, Sleman, Yogyakarta. The samples were cassava (Manihot esculenta Crantz), water yam (Discorea Alata), intoxicating yam (Dioscorea hispida Dennst), canna lilly (Canna discolor L), and taro (Colocasia esculenta). The qualitative test was performed by cementing the sample with aquadest and 10% tartrate acid and then covering the erlenmeyer that containing the sample with dry filter paper immersed in saturated picric acid and dampened with 8% sodium carbonate and then heating it. Quantitative tests were performed using a spectrum 20 with a wavelength of 590 nm. This quantitative test is based on forming a blue hydrindantin complex at pH 12 when cyanide is reacted with a ninhydrin complex. The results showed that in qualitative test, sample containing cyanide was indicated by the change of color of filter paper from yellow to brownish red. Quantitative results show that cyanide contained in sample as varies levels. The cyanide levels through the various species of yams were 0.1098 mg / 100g for cassava 0.049 mg/100 g for water yam, 0.1394 mg/100g for intoxing yam, 0.0896 mg/100 g for canna lilly and 0.0680 mg / 100g for taro.